Effect of acupuncture on pain and substance P levels in middle-aged women with chronic neck pain - Ko, Jade Heejae; Kim, Seung-Nam (Frontiers in Neurology, 2023)
Chronic neck pain is a leading health issue affecting a significant proportion of the global population. Multiple treatment options for chronic neck pain include anti-inflammatory drugs and analgesics. Acupuncture has been widely used for the treatment of chronic pain. In this study, we aimed to determine the efficacy of acupuncture for female patients with chronic neck pain. Twenty-three participants were enrolled in the study, and participants waited 4 weeks without acupuncture treatment and then received 4 weeks of treatment. One-way ANOVA with repeated measures was used to determine differences in the visual analogue scale (VAS), neck disability index (NDI), and substance P (SP) over time. The subjects’ pain intensity and degree of disability due to neck pain were measured as primary outcomes. SP in the blood was also analyzed as a secondary outcome. There was no significant difference between the VAS score and NDI value of baseline and after 4 weeks waiting. However, there was an improvement in both VAS and NDI after 4 weeks treatment. SP level was decreased after 4 weeks treatment. We could conclude that acupuncture is effective in alleviating chronic neck pain. Moreover, our findings revealed the efficacy of acupuncture on chronic pain with potential underlying biological mechanisms.